Escaping the fragility/conflict poverty trap: How the interaction between service delivery, capacity development and institutional transformation drives the process of transition out of fragility - Mamadou Dia (South Centre, 2022)
The main background and rationale of this research paper is that while donors' scaled-up engagements in Fragility and Conflict-affected States (FCS) during the last decades were a resounding success in terms of official development resources devoted to FCS, the value for money compared to the ultimate goal of helping these countries move out of fragility was well below expectations. The World Bank ex post evaluation of the results of its engagement in FCS found that 80 percent of FCS that were on the harmonized list of fragile situations in 2012 remain on it today and the author's observational study of a sample of 16 African FCS over a 5-year period found that only 1 made progress while 12 stayed in the status quo and 3 regressed. The main reason for the poor value for money is that while International Financial Institutions (IFIs) have spent tremendous amount of resources and brain power to build an excellent knowledge base about fragility and resilience, no such efforts were made to help understand the process and stages for a successful transition from fragility to resilience. The purpose of this paper is to help fill the knowledge gap in order to encourage development partners engaging in FCS to shift from a Fragility-focused to a Transition-based Engagement Business Model and thus minimize the risks of the poor value for money results. The paper will do so by outlining a methodology and framework for a better understanding of the process and a road map for a successful transition from fragility to resilience with measurable stage/sign posts and benchmarks to evaluate progress and necessary adaptation to donors' strategic and operational support instruments.
Keywords: 300; Capacity Development; Conflict; COVID-19; Development Partners; Fragility; Fragility and Conflict-affected States (FCS); Institutional Transformation; International Financial Institutions (IFIs); Pandemic; Poverty; Resilience; Service Delivery; Transition-based Engagement Partnership (TEP)